Ijtihad in Bridging Revelation and Modern Life Realities and Its Implementation in Islamic Education - Dede Ridho Firdaus; Rikil Amri (Faculty of Teacher Training and Education, Palangka Raya University, Central Kalimantan, Indonesia. Pos Code 73112, 2025)
This particular research focuses on ijtihad and its role as a processor in Islam within the context of revelation and the modern day realities of the world. The rationale behind this research is the necessity for a Sharia compliant legal system in the context of the social, technological, and cultural changes, hence the need for a ‘contextual’ and ‘adaptive’ legal approach. This particular research focuses on the challenge of how ijtihad is able to respond to current problems while preserving Islamic teachings to the bare minimum. The methodology adopted in this particular study is a literature survey and qualitative research of Islamic writings as well as modern day fatwas on the practice of ijtihad. The findings of the study suggest that ijtihad is necessary and instrumental in Islamic law in the context of modern Islamic critical thinking within a multidisciplinary context of Islam in Contemporary ideas of finance, bioethics, and information technology (it). It is therefore justified that ijtihad remains a principle instrument interlinking the revelation and the modern day problems of the Muslim world.